Individual variation in predator behavior and demographics affects consumption of non-native prey. (31st March 2015) - Pintor, Lauren M.; Byers, James E.
Lay Summary: In a series of laboratory experiments, we show that female predatory crabs that are smaller, less aggressive, and less exploratory are more likely to eat a recently introduced nonnative prey that has invaded oyster reef communities along the coast of Georgia. The unwillingness of the entire native predator population to consume this new prey may contribute to these nonnative prey escaping their natural enemies and becoming invasive pests. Abstract : Non-native species can serve as a prey resource for native predators. Yet because there is often no shared evolutionary history between the predator and prey, individuals within a predator population may vary greatly in their willingness to consume a recently introduced, yet profitable prey. Here, we measured individual variation in diet, behavior, and demographic traits of the native predatory mud crab, Panopeus herbstii, and evaluated how these traits influenced an individual's consumption of a recently introduced, non-native crab, Petrolisthes armatus, using both simultaneous and no-choice assays. These same individual predatory mud crabs were also assayed to quantify their antipredator reaction and exploratory behavior. Results indicated significant variation in the diets of individual predators with 45% specializing on native mussels, 14% specializing on non-native Petrolisthes, and the remainder eating multiple prey species. When given a choice of alternative prey, individual Panopeus predators that consumed a larger proportion of Petrolisthes were female, smaller, and more likely to flee in response to predators. When given no choice of alternative prey, Petrolisthes was consumed more frequently by Panopeus that were female and less exploratory. We suggest that individuals that more readily consume non-native Petrolisthes may be attempting to reduce competition with conspecifics that are larger, more aggressive, exploratory, and male. Our results suggest that at least initially following invasion, adoption of a non-native prey species into the diet of a native predator may not occur universally within the population. Such nonuniform predation pressure could contribute to the non-native prey's release from natural enemies.